Analysis of curative effect of percutaneous coaxial large channel endoscopic lumbar interbody fusion in the treatment of degenerative lumbar spinal stenosis - Feng, Pin; Kong, Qingquan; Zhang, Bin; Liu, Junlin; Ma, Junsong; Hu, Yuan (Frontiers in Surgery, 2022)
Objective To investigate the clinical efficacy and technical points of Percutaneous Coaxial Large-channel Endoscopic Lumbar Interbody Fusion (PCLE-LIF) in the treatment of degenerative lumbar spinal stenosis. Methods The clinical data of patients with single-segment degenerative lumbar spinal stenosis who underwent PCLE-LIF surgery from January 2019 to June 2021 were retrospectively analyzed. Surgery-related data included symptom duration, operation time, hospital stay, and complication rate. Functional score data included low back pain and lower extremity pain VAS score, ODI score, and MacNab criteria were used to evaluate clinical effects. The Brantigan criteria were used to evaluate the interbody fusion. Results There were 62 patients in this group, including 35 males and 27 females. The surgical sites were all lower lumbar spine, including 35 cases of lumbar L4/5 and 27 cases of L5/S1. The length of hospital stay was 7.7±1.4 days. All patients were followed up regularly for 1 year. The interbody fusion rate was 93.5% at 1 year after operation. There were 2 cases of numbness, 2 cases of nerve edema and pain, 1 case of cage displacement, and 1 case of pedicle screw loosening. The complication rate was 9.6%. The VAS scores of low back pain 1 day before surgery, 3 days, 3 months and 1 year after surgery were 4.48±1.06, 0.84±0.81, 0.40±0.56, 0.39±0.69, and the VAS of lower extremity pain at each time point of appeal were 5.58±0.98, 0.91±0.58, 0.31±0.46, 0.19±0.40. The ODI scores at 1 day before surgery, 3 months and 1 year after surgery were 60.01±6.21, 15.58±2.84, 8.82±2.15. The ODI scores and VAS scores of low back pain and lower extremity pain at each follow-up time point after operation were significantly lower than those before operation (P<0.05). The 1-year follow-up after operation was evaluated by the modified MacNab standard, and the results were excellent in 36 cases, good in 23 cases, fair in 3 cases, and poor in 0 cases, with an excellent and good rate of 95.2%. Conclusion Percutaneous coaxial large-channel endoscopic lumbar interbody fusion in the treatment of degenerative lumbar spinal stenosis has good short-term efficacy and high safety, and is worthy of popularization